1983
DOI: 10.1037/h0080735
|View full text |Cite
|
Sign up to set email alerts
|

The construction and development of the Miller Marital Locus of Control scale.

Abstract: The growing interest in and use of goal-specific locus of control scales to investigate the significance of internal-external control beliefs in a variety of important life areas has prompted the development and preliminary validation of the Miller Marital Locus of Control scale (MMLOC). The 44-item scale measures the extent to which respondents view reinforcements in the marital domain as being contingent upon their own efforts and abilities, or as being due to factors outside their control. Results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 29 publications
0
42
0
4
Order By: Relevance
“…МЛОЦ скале (ен:л. The Marital Locus of Control Skale; Miler, Lefcourt & Ware, 1983). Скала се сасLоји о9 34 сLавке, а резулLаLи се :руDишу у 9ве независне суJскале: инLерни (16 сLавки: 3,6,7,9,12,14,15,16,18,20,21,24,26,29,31,33) и ексLерни (18 сLавки: 1,2,4,5,8,10,11,13,17,19,22,23,25,27,28,30,32,34) локус конLроле, чији се резулLаLи о9војено инLерDреLирају.…”
Section: методолошки деоunclassified
“…МЛОЦ скале (ен:л. The Marital Locus of Control Skale; Miler, Lefcourt & Ware, 1983). Скала се сасLоји о9 34 сLавке, а резулLаLи се :руDишу у 9ве независне суJскале: инLерни (16 сLавки: 3,6,7,9,12,14,15,16,18,20,21,24,26,29,31,33) и ексLерни (18 сLавки: 1,2,4,5,8,10,11,13,17,19,22,23,25,27,28,30,32,34) локус конLроле, чији се резулLаLи о9војено инLерDреLирају.…”
Section: методолошки деоunclassified
“…Bu bağlamda, kendi yaşamlarından sorumlu oldukları değerlendirmesini yaparak, buna uygun davranış ortaya koyarlar (Yeşilyaprak, 2004). İçsel kontrol odağına sahip bireyler dışsal kontrol odağına sahip bireylere oranla stres ve anksiyete ile baş etmede daha başarılı (Arslan, Dilmaç & Hamarta, 2009); alkol bağımlılığından kurtulmada daha iyi (Yeh, Lee & Hwang, 2008); daha sorumluluk sahibi (Altın & Karancı, 2008); kişiler arası ilişkilerde daha aktif ve atılgan (Yeşilyaprak, 2005); kendilik algılarının daha fazla (Loosemore & Lam 2004), kendilerini sağlıklı hissetme algılarının daha etkin (Ozolins & Stenstrom, 2003); daha iyimser (Carifio & Rhodes, 2002); içsel motivasyonlarının (Fazey & Fazey 2001) ve başa çıkma becerilerinin (Elise, Bryan & Kathleen, 1998) daha yüksek, problem çözmede daha başarılı (Serin & Derin, 2008); karar vermede daha etkili (Çoban & Hamamcı, 2006;Kaplan, Reneau & Whitecotton, 2001); öz yeterliliği ve umut düzeyi daha yüksek (Carifio & Rhodes, 2002) (Leone & Burns, 2000), İç-dış Kontrol Odağı Ölçeği (Rotter, 1966), Nowicki-Strickland İç-Dış Kontrol Odağı Ölçeği (1973), öğretmenlik kontrol odağı ölçeği (Rose & Medway, 1981), iş kontrol odağı ölçeği (Spector, 1988), evlilik kontrol odağı ölçeği (Miller, Lefcourt & Ware, 1983), ebeveynlik kontrol odağı ölçeği (Campis, Lyman & Prentice-Dunn, 1986), akademik kontrol odağı ölçeği (Trice, 1985) gibi birçok ölçme aracı bulunmaktadır. Ülkemizde ise, Dağ (2002) tarafından geliştirilen Kontrol Odağı Ölçeği ve yurt dışından adapte edilen birçok ölçme araçları bulunmaktadır (Öngen, 2003).…”
Section: Introductionunclassified
“…Recent reviews of the locus of control literature revealed a good number of studies about the relation between the type of control and marriage (Doherty, 1981;Sheth, 2015). According to Miller, Lefcourt, and Ware (1983), locus of control is related to a variety of variables, such as marital problem solving. According to Lundberg (2012) stable partnership is bounded to higher incomes, improved health and happiness, and positive child outcomes.…”
Section: Psychological Thoughtmentioning
confidence: 99%